2016
DOI: 10.3389/fmicb.2016.00092
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Rhizosphere Effect on Available Carbon Sources, Phenanthrene Degradation, and Active Microbiome in an Aged-Contaminated Industrial Soil

Abstract: Over the last decades, understanding of the effects of plants on soil microbiomes has greatly advanced. However, knowledge on the assembly of rhizospheric communities in aged-contaminated industrial soils is still limited, especially with regard to transcriptionally active microbiomes and their link to the quality or quantity of carbon sources. We compared the short-term (2–10 days) dynamics of bacterial communities and potential PAH-degrading bacteria in bare or ryegrass-planted aged-contaminated soil spiked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 90 publications
3
24
0
Order By: Relevance
“…This means that the planting layout of the poplars (0.5 × 2m) was effective in ensuring that their root development positively stimulated the overall microbial community in each planted plot. The positive "rhizosphere effect" has been reported by other authors [26,27] and was presumably due to the root surface releasing several organic compounds into the adjacent soil. Roots release low-molecular-weight exudates (e.g.…”
Section: Discussionsupporting
confidence: 65%
“…This means that the planting layout of the poplars (0.5 × 2m) was effective in ensuring that their root development positively stimulated the overall microbial community in each planted plot. The positive "rhizosphere effect" has been reported by other authors [26,27] and was presumably due to the root surface releasing several organic compounds into the adjacent soil. Roots release low-molecular-weight exudates (e.g.…”
Section: Discussionsupporting
confidence: 65%
“…It has been previously observed that abundance of PAH-RHDα gene was often changed by root exudates23, organic matter24 and pH25. Controlled experiments with more comprehensive and sensitive tests, for example the transcription activities analysis2627 are therefore required to reveal the effects of PAH pollution on degrader community.…”
Section: Resultsmentioning
confidence: 99%
“…While there is accumulating evidence that plant traits, and in particular root traits, can predict soil faunal and microbial community structure and functioning (De Vries et al 2012b;Grigulis et al 2013;Legay et al 2016), there is only limited evidence that links plant traits to soil microbial networks. For example, it has been shown that specific compounds in root exudates can promote the formation of bacterial clusters (Thomas & Cebron 2016). In addition, in a mesocosm study with eucalyptus seedlings, networks of ammonia-oxidising archaea were more connected and had more modules in soil under elevated CO 2 than those under control conditions, presumably through changes in below-ground plant C inputs (Hu et al 2016).…”
Section: The Rhizosphere Interactions For Sustainable Agriculture Modelmentioning
confidence: 99%